The Users’ Comments on Tiktok Account of Ishowspeed: A Study Morphological Errors Analysis - Suparwoto Sapto Wahono; Nadia Dwi Rahmawati; Sulistiana Khofifah (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
This study aims to analyse morphological errors found in the comment section of the TikTok account @iShowSpeed, focusing on inflectional, derivational, and compound morphology. Researchers used a qualitative descriptive approach. The data were collected through online observation on social media and document which were screenshot from social media.  The data were collected using purposive sampling from users written comments on Tiktok account @iShowSpeed. The results showed that the most frequent errors were related to grammatical realization, which encompasses both syntactic and morphological issues. The most common issues were verb phrase errors, such as missing auxiliary verbs or incorrect tense usage (e.g., "Amy better than you" instead of "Amy is better than you"). Additionally, derivational errors were also common, including incorrect word forms like "retirement" used instead of "retiring," or misused affixes such as "employee" employed as a verb. In contrast, compound morphology showed fewer errors, with correct examples like “livestreams” being commonly used. These findings indicate that users often prioritize speed and informality in digital communication, leading to frequent morphological inaccuracies. This research highlights the influence of social media on language use and provides insight into the need for better morphological awareness, especially for non-native English users engaging in online discourse. The findings are crucial for developing targeted interventions in language learning curricula and informing digital literacy programs on effective online communication skills.